The effect of nano-particles concentration AL2O3 on the performance in compression refrigeration system - Sakhir, Abbas Alwi; Mahmoud, Rawnak Khalid (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
An experimental study of the performance of compression refrigeration system. when adding nanoparticles of 20 nm size and mixed with PAG oil. After preparing the nano-lubricant, it is injected into the compressor and the Refrigerant R134a is charged. in the present work is used different volume fractions (0.2%, 0.4%, 0.6%) of AL2O3 nano-particles to study the performance of the refrigeration tester. Energy consumption check and freezing capacity test. Experimental results have shown that the system operates safely and normally, the maximum improvement of the coefficient of performance is 32.219% at a concentration of 0.6% at temperature 40°C. In addition, power consumption decreases from 4% to 22%, and the temperature decreases by (40 °C - 17 °C). The cooling effect of the system increases when the concentration of the nano-particles increases. It can be inferred that nano-refrigerant can be competitive and economically efficient for use in vapour compression systems.